REPUTATION MANAGEMENT AND MARKETING POLICY OF THE ENTERPRISE - KOROL, Volodymyr; IABLON, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the issue of forming and using a positive image of an enterprise. It is emphasized that in conditions of market and information transparency, active use of digital technologies and digital communications, social networks, etc., the reputation of an enterprise becomes an important aspect and even a means of competitive struggle, on the one hand, as well as a marketing method and a means of supporting the promotion, positioning and sales of products in the markets, on the other hand. Therefore, the purpose of the article is to generalize existing and develop new methodological and applied provisions in the field of reputation management and the use of the enterprise’s marketing policy tools. It is argued that if the outlines of a positive image and reputation of a business entity are formed within its internal management system, then their dissemination into the external information (and not only) space is carried out by means of the enterprise’s marketing policy. Moreover, as shown in the study, the opportunities for such measures and actions have significantly improved along with the spread of information technologies, the formation of an information society, as well as the increasingly active use of Internet marketing and information and communication marketing technologies, digital business communications of enterprises. The scientific novelty of the research results concerns the further development of the theoretical and methodological connection between the aspects of reputation management and the marketing mix complex. The applied significance of the research results lies in the significant enrichment of the marketing tools of enterprises, in particular in the field of public relations.